A comprehensive study on acute non-traumatic abdominal emergencies - Malviya, Ajay; Hussain, Ashfaque; Bulchandani, Hitesh P.; Bhardwaj, Girish; Kataria, Subhash (International Surgery Journal, 2017)
Background: Abdominal pain is one of the most common reasons for visit to the emergency room. Acute appendicitis is the commonest cause. An accurate diagnosis is essential for the correct treatment, which in many cases will prevent the death of the patient. Mainstay of diagnosis is history and physical examination. If this information is inadequate to establish a diagnosis and urgent or immediate operation is unnecessary, the periodic re-examination helps document the progression of the disease and often avoids unnecessary surgical intervention. Today the combination of improved diagnostic procedures, antibiotic and better anaesthesia and preoperative and postoperative patient care has led to a decrease in morbidity and mortality of patients with acute abdomen. The objective of this study was to determine the various causes of non-traumatic acute abdominal emergencies, their incidence, management and mortality in both sexes and all age groups >12 years age. Methods: The Study was conducted on 1353 patients of non-traumatic abdominal emergencies admitted in the department of surgery, associated group of hospitals attached to Dr. Sampurnanand Medical College, Jodhpur over a period of 1 year extending from 1st January 2015 to 31st December 2015. Results: Most common cause of acute non-traumatic emergency in our study is acute appendicitis 61.71% of the patients. Out of 1353 cases of non-traumatic acute abdominal emergencies, 217 (16%) were managed conservatively while 1136 (84%) were operated. 96.64% cases of acute appendicitis were operated and only 3.36% underwent conservative management. The rate of operative intervention in acute intestinal obstruction and acute cholecystitis was 89.09% and 85.71% respectively. 81.89% cases of hollow viscus perforation were operated while 18.11% were treated conservatively. Only 18.18% cases of liver abscess underwent operation while all patients of Meckel’s Diverculititis were managed operatively. All patients of acute pancreatitis were managed conservatively. Overall mortality in our study of acute non-traumatic abdominal emergencies was 3.39%. Conclusions: It can be concluded that acute non-abdominal emergencies admitted in the hospital constitute a major chunk of surgical patients, majority requiring operative management with limited mortality.